Changes of wrist motion range by changing forearm position in healthy men - Narita, Aya; Fujii, Hiromi; Naito, Akira; Sotokawa, Tasuku; Suzuki, Katsuhiko; Naganuma, Makoto; Sato, Toshiaki; Akiyama, Takao; Hashizume, Wataru; Nito, Mitsuhiro; Nakano, Haruki; Fujita, Takaaki (Structure and Function, 2014)
Changes of a wrist motion range by changing the forearm position were studied. 2-D trajectories (coronary plane) of the head of the third metacarpal of the right hand during a wrist full circumduction movement in the 90° pronated (prone: P), 0° pronated (neutral or semiprone: SP), and 90° supinated (supine: S) position of the forearm were plotted in twenty healthy right-handed men. Trajectories were ellipsoid in shape in every forearm position. The range of extension and adduction was larger in SP than in P and that of flexion was the largest in P, next was in SP and smallest in S. The area of the ellipse was larger in P and SP than in S. The long axis of the ellipse tended to be longer in SP than in S and the short axis to be in P and SP than in S. Changing the position from P to SP and from SP to S resulted in approximately 20° step counterclockwise rotation of the long axis. These findings suggest that the range is complicatedly changed by changing the forearm position, it becomes smaller in S, and the direction, in which wrist swing motion becomes larger, turns counterclockwise with supinating the forearm.